Different learning styles in acquisition of declarative and procedural knowledge / Ammuthavali Ramasamy - Ammuthavali, Ramasamy (2005)
Conducting Visual Basic 6.0 training in Tenaga Nasional Berhad creates problems due to differences in cognitive skill among the executives and the non-executives as the target participants. This skill varies among them in the modes of learning style, types of knowledge and problem-solving method. Thus we propose a web-based training prototype as an aid for learning. The prototype is meant to teach simple concepts of Visual Basic 6.0. It consists of two different learning modules: the declarative knowledge module and procedural knowledge module. It directs the learners to their respective learning modules based on their learning styles. The prototype contains instructional design methodologies that are derived from behaviorism, cognitivism and constructivism learning theories. Evaluations done on the prototype show that it manages to identify individuals according to the target audiences and accommodates training needs of both groups.